Isolation of enterotoxigenic Bacteroides fragilis from Bangladeshi children with diarrhea: a controlled study. - Sack, R B (1994)
We undertook a controlled study of children younger than 5 years in Bangladesh to determine whether enterotoxigenic Bacteroides fragilis (ETBF) was associated with diarrhea in this population. ETBF was isolated from 22 (6.1%) of 358 patients and 5 (1.2%) of 425 controls (P = 0.0001). In children younger than 1 year, however, low isolation rates (2 to 3%) were found in both patients and controls. In children older than 1 year, the rates were significantly higher in children with diarrhea (16 [9%] of 177) than in controls (2 [1%] of 264; P = 0.00001). When children with mixed infections with other known diarrheal pathogens were removed, the differences in children older than 1 year were still significant (7 [4%] of 177 versus 2 [1%] of 264; P = 0.033). The syndrome associated with ETBF was secretory in nature, with watery diarrhea, and of mild severity. These epidemiological and clinical findings are similar to those from a previous study of White Mountain Apaches in the United States and are the first to suggest that ETBF may also be an important diarrheal pathogen in other geographic areas and in the developing world where diarrhea is highly endemic.